IADC/SPE Drilling Conference 2006
DOI: 10.2118/98988-ms
|View full text |Cite
|
Sign up to set email alerts
|

PDC Bits: All Comes from the Cutter/Rock Interaction

Abstract: PDC drill bit performances in hard rock has been greatly improved during the last decades by innovations in PDC wear, impact resistance and better vibrations understanding. The bit design is generally done by balancing the bit, distributing uniform wear along the profile and achieving high drillability and steerability. To obtain required drilling performances, drill bit designer adjust features such as profile shape, gage and mainly cutter characteristics (shape, type and orientation). Cutter rock interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…Furthermore, it contradicts the classical static assumption which states that cutting forces do not depend on the cutting velocity [31]. Indeed, most existing cutting models are static [37,12,11,30,16].…”
Section: The Pure Torsional Approachmentioning
confidence: 98%
“…Furthermore, it contradicts the classical static assumption which states that cutting forces do not depend on the cutting velocity [31]. Indeed, most existing cutting models are static [37,12,11,30,16].…”
Section: The Pure Torsional Approachmentioning
confidence: 98%
“…Operating parameters as weight and torque on bit, defined for a constant penetration speed, could be considered as independent of the number of bits [7]. This condition is assumed by a correct cutters repartition on the bit, which ensures a homogenized wear on every PDC [8]. Therefore, wear behavior and drilling performance information based on single cutter experiments are relevant and can be extrapolated to understand the whole tool behavior.…”
Section: Wear Rate Analysismentioning
confidence: 99%
“…The assumption of the bit being a cylinder and not a discrete number of blades implicitly assumes the cutting force at each cutter to increase linearly with its tangential velocity. In literature (Langeveld 1992;Neubert 1997;Gerbaud 2006;Ernst 2007) it can be found that the velocity of a cutter does not influence the cutting forces. Cutting forces are nearly only dependent on the orientation of the cutter and the depth of cut DOC.…”
Section: Blade Aggressivenessmentioning
confidence: 99%
“…This is not the case for bit aggressiveness. In literature several cutter force models can be found showing the force at a cutter being only dependent on the area of cut and being independent of the cutter velocity, see (Langeveld 1992;Neubert 1997;Gerbaud 2006;Ernst 2007). The blade aggressiveness regards these general cutting force model assumptions and in this way provides a complete separation of the influences of drilling diameters D and cutting structure aggressiveness µ.…”
Section: Nomenclaturementioning
confidence: 99%